Postmortem diagnosis of Factor V Leiden from paraffin wax embedded tissue - Webb, J S (1996)
Activated protein C resistance resulting from Factor V Leiden is an important inherited thrombophilia disorder which is found in 3.5% of people in the UK. The genetic defect can be detected using the PCR and the diagnosis can be made postmortem from paraffin wax embedded tissue. The presence of Factor V Leiden should be sought in all cases of unexplained sudden death resulting from venous thromboembolism.